2017
DOI: 10.1007/s11914-017-0377-9
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in Ewing Sarcoma, Osteosarcoma, and Malignant Peripheral Nerve Sheath Tumors

Abstract: Recent work has assessed the role(s) of Wnt signaling within these cell types. This review provides an overview of the mechanistic insights that have been gained from a number of recent studies to set the foundation for potential therapeutic applications. Wnt signaling has emerged as a potentially critical pathway in maintaining the growth of these types of tumors. Given the fact that many new inhibitors of the pathway have recently or will soon enter Phase 1 clinical trials, it is likely that assessment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 88 publications
1
27
0
1
Order By: Relevance
“…The functional role of the Wnt signaling pathway in OS is not completely understood ( 23 ). A number of studies support the idea that the Wnt signaling pathway serves an anti-tumorigenic effect in OS ( 24 26 ), whereas other studies suggest that aberrant activation of the canonical Wnt signaling pathway serves an important role in OS initiation, maintenance and resistance to chemotherapy ( 27 , 28 ). In addition, a large number of studies have demonstrated that miRNA has an effect on the development of OS by targeting the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The functional role of the Wnt signaling pathway in OS is not completely understood ( 23 ). A number of studies support the idea that the Wnt signaling pathway serves an anti-tumorigenic effect in OS ( 24 26 ), whereas other studies suggest that aberrant activation of the canonical Wnt signaling pathway serves an important role in OS initiation, maintenance and resistance to chemotherapy ( 27 , 28 ). In addition, a large number of studies have demonstrated that miRNA has an effect on the development of OS by targeting the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA PDIA3P activates the Wnt/β-catenin signaling pathway. To determine the underlying mechanism by which PDIA3P affects NSCLC progression, RT-qPCR and western blotting were performed to examine the effects of PDIA3P on the Wnt/β-catenin pathway, which is frequently aberrantly activated in human cancer (19). The results showed that PDIA3P inhibition decreased both the mRNA and protein expression levels of β-catenin and c-myc, and increased the expression levels of GSK-3β in A549 cells ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…As a bone‐forming agent and activator of the canonical osteoanabolic Wnt‐signalling pathway, a potential for carcinogenesis has been raised with romosozumab. The WNT‐signalling pathway has been related to different human cancers . In human osteosarcoma tissue, the presence of Wnt receptor LRP5 correlates with a worse prognosis .…”
Section: Dual Actions Drug: Romosozumabmentioning
confidence: 99%